The Place and Significance of English in Business Communication in India - Devina Kaul Krishna, (Journal of Human Development and Communication (JoHDeC), 2025)
Nowadays in India, multilingualism has become a trend with English language gaining popularity alongside the existing language (Hindi). English is regarded as a situation for flourishing amalgamation into the global economy and becomes a priority of the nation guiding principle. The purpose of this paper is to show that English is at present principally used at a workplace and for specific purposes such as emails, writing a business letter, memo etc. In terms of motives of learning English, development and personal growth have been mentioned as the most common reasons for English proficiency among Indian business professionals. It discusses at length how English is indeed the language of the corporate world. Ranging from business meetings to negotiations across India, English is used for everything. Last but not least, it lays stress on the main reasons for the need of English at present stage of India’s development and how English proficiency is a must for a professional profile.